Models and activities of critical care outreach in New Zealand hospitals: results of a national census. Issue 4 (19th February 2014) - Pedersen, Anne; Psirides, Alex; Coombs, Maureen
Abstract: Aim: To review clinical models and activities of critical care outreach (CCO) in New Zealand public hospitals. Methods: Data were collected using a two‐stage process. Stage 1 consisted of a cross‐sectional descriptive online survey distributed to nurse managers of all CCO in New Zealand. Stage 2 requested that all respondent sites supply outreach documentation for analysis. Results: Twenty acute care public hospitals replied to the data request (100%). Nine hospitals (45%) had CCO and completed the survey. There was considerable diversity in the models of CCO used. All nine hospitals had CCO that were nurse‐led; 66% of these had intensive care medical input. There was variation in the size and scope of each CCO with only 4 (44%) sites providing 24‐h clinical cover. The majority of referral requests made to CCO were for ward‐based reviews (mean: 57%) and intensive care discharge reviews (mean: 31%). The most frequently performed activity was provision of support to ward staff (89%). All CCO routinely collected data on activities across a range of clinical areas. Conclusion: Less than half of the public hospitals in New Zealand have a CCO service despite national recommendations that every hospital utilize one to support deteriorating ward patients. New Zealand hospitals that have critical care outreach have adopted recognized international models and adapted these to meet local demands. Whilst the evidence base demonstrating impact of critical care outreach continues to be established, international support for critical care outreach continues. Given this, critical care outreach should be more widely available 24/7 and activities standardized across New Zealand to align with national recommendations. Relevance to clinical practice: Critical care outreach service models and activities in New Zealand hospitals continue to be diverse. Awareness of these variances will help influence critical care outreach service development and regional integration.